2004
DOI: 10.3748/wjg.v10.i1.53
|View full text |Cite
|
Sign up to set email alerts
|

Superantigen-SEA gene modified tumor vaccine for hepatocellular carcinoma: Anin vitrostudy

Abstract: AIM:To construct an eukaryotic superantigen gene expression vector containing the recombinant gene of SEA and CD80 molecule transmembrane region (CD80TM), and to express staphylococcus enterotoxin A (SEA) on the membrane of hepatocellular carcinoma (HCC) cell to form a superantigen gene modified tumor vaccine for HCC. METHODS:SEA and linker-CD80TM gene were amplified through PCR from plasmid containing cDNA of SEA and CD80. Gene fragments were then subcloned into the multiple cloning sites of retroviral vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“… 9 In another study, Lu and colleagues found that the construct obtained from fusing cloned-SEA into pLXSN with linker-CD80TM can be used as an antitumor agent. 26 The studies of Yue et al and Xu et al used pET42b (+) and pET-22b (+) as expression vectors for cloning of SEA, respectively; they also used BL21(DE3) as an expression host, 27 , 28 whereas in our study, entA gene was cloned into the pET-21a vector and we believe that, this is the first report of expression of entA gene into pET-21a as an expression plasmid; also in our study, BL21(DE3) was used as an expression host like the other study mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“… 9 In another study, Lu and colleagues found that the construct obtained from fusing cloned-SEA into pLXSN with linker-CD80TM can be used as an antitumor agent. 26 The studies of Yue et al and Xu et al used pET42b (+) and pET-22b (+) as expression vectors for cloning of SEA, respectively; they also used BL21(DE3) as an expression host, 27 , 28 whereas in our study, entA gene was cloned into the pET-21a vector and we believe that, this is the first report of expression of entA gene into pET-21a as an expression plasmid; also in our study, BL21(DE3) was used as an expression host like the other study mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…T-cells have multifarious antitumor effects via releasing tumor-suppressive cytokines (interferon γ [IFN-γ] and tumor necrosis factor α [TNF-α]) or cytotoxic effector molecules such as perforin, 22,25 –27 but generally the number of tumor-specific T-cells is insufficient to mediate potent antitumor responses against progressive tumor growth. 34…”
Section: Discussionmentioning
confidence: 99%
“…Their efficacy has also been considered superior to exogenous cell factor. With the development of relevant theory, superantigens have attracted much attention of studies [1,2]. Earlier studies applied superantigens independently in anticancer therapy.…”
Section: Introductionmentioning
confidence: 99%